Experimental assessment of energy consumption: a comparative study between motor-controlled and valve-controlled cylinders in knuckle boom crane operations - Zhao, Wei; Ebbesen, Morten Kjeld; Hansen, Michael Rygaard; Andersen, Torben Ole (Frontiers in Mechanical Engineering, 2025)
This paper experimentally assess the energy consumption of a laboratory knuckle boom crane utilizing two proposed two-motor-two-pump (2M2P) motor-controlled hydraulic cylinders (MCC) in comparison to two conventional valve-controlled hydraulic cylinders (VCC). Experimental results demonstrate that using the motor-controlled crane instead of the valve-controlled crane results in 60%–64% total energy savings. In conclusion, this study highlights the practical suitability of the 2M2P MCCs for real-world applications, showcasing their enhanced energy efficiency compared to conventional VCCs.